Sistematização de práticas de assistência técnica e extensão rural (SEPER): análise da política pública de aquisição de alimentos da agricultura familiar para servidores públicos municipais de Chiapetta/RS (PAASP) - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This work analyzes the results provided by the Systematization of Rural Extension Practice Experience (SEPER) in the context of the Food Acquisition Program for Public Servants (PAASP) of Chiapetta/RS. It is a comprehensive study that seeks to analyze and document in detail the implementation and results of this program, as well as reporting rural extension practices in the specific context of the municipality of Chiapetta, located in Rio Grande do Sul. SEPER was carried out by the Interdisciplinary Group of Studies in Rural Development (GIEDER). SEPER was built from different stages where the research consisted of training with the local Technical Assistance and Rural Extension Company (EMATER); study trip to understand the dynamics of PAASP; selection of interviewees, with the aim of providing a comprehensive view of rural extension practices. During data collection, the diversity of foods provided by the program became evident, contributing to food security. The study consists of a contextualization of the Chiapetta region, highlighting the ocioeconomic scenario and the conditions that motivated the adoption of the program. SEPER was based on a detailed methodology, following visits to different actors in the program, such as agribusinesses, family producers, city hall and delivery locations. The effective strengthening of family farming was highlighted, with positive results in food security for public servants who benefited. The stimulus to local production was evident, reflected in the reduction of rural exodus and support for sustainable agricultural practices. The analysis of data collected during SEPER provided valuable insights into the transformative role of PAASP, outlining a scenario of effective contribution to the socioeconomic and environmental development of the region.
Systematization of technical assistance and rural extension practices (SEPER): analysis of the public policy for purchasing food from family farming for municipal public servants in Chiapetta/RS (PAASP)
Keywords: Agricultura familiar; Desenvolvimento local; Impactos sociais e econômicos; Políticas Públicas; Family farming; Local development; Social and economic impacts; Public policies; CNPQ::CIENCIAS AGRARIAS